41‐2: Invited Paper: An Advanced High‐Dynamic‐Range LCD for Smartphones. Issue 1 (29th May 2019) - Zheng, Binyi; Deng, Zhuo; Zheng, Jianping; Wu, Ling; Yang, Wenbin; Lin, Zongwei; Wang, Hailiang; Shen, Poping; Li, Junyi
Abstract : An advanced high dynamic range LCD with the excellent performance was developed. The HDR LCD technology is mainly about mini LED local dimming design which includes LED pitch, optical field distribution, and optical film stack. Improved methods about HDR LCD were studied, which make it a promising technique for a smartphone.